أثر سياسات التسويق الداخلي في تعزيز الالتزام التنظيمي لدى العاملين (دراسة حالة مؤسسة نافطال Gpl بولاية بشار) - بودية هاجر; بن سالم عبد الحكيم (جامعة الوادي University of Eloued, 2024)
The study aimed to identify the role of internal marketing in achieving organizational commitment among employees of the Naftal GPL Branch BECHAR, by presenting selected internal marketing strategies (training and development of employees, internal communication, incentive systems and administrative empowerment) and analyzing their impact on enhancing the organizational commitment of employees, and used the descriptive analytical approach to the terminological control of the study variables and the presentation of previous studies associated with them .It also relied on the statistical program SPSS to analyse the answers of the study sample, which amounted to 40 respondents, and the results found that there is a strong impact of the dimensions of internal marketing on organizational commitment, and that the dimension of administrative mastery is the most influential dimension in enhancing organizational commitment among employees of the institution under stud
The impact of internal marketing policies in enhancing organizational commitment among employees -Case study of Naftal Corporation GPL in Bashar State
Keywords: تسويق داخلي; إلتزام تنظيمي; internal marketin; organizational commitmen